The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.prs.0000041395.02699.b7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduction Mammaplasty on Pulmonary Function and Symptoms of Macromastia

Abstract: A number of studies have documented subjective improvement in somatic and psychological symptoms following breast reduction surgery. Objective data demonstrating improved postoperative function have been more difficult to assess, and particularly with respect to pulmonary function, the results have been contradictory. In this prospective study, patients completed a comprehensive preoperative questionnaire modified from the American Thoracic Society Division of Lung Diseases Epidemiology Standardization Project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 16 publications
3
30
0
4
Order By: Relevance
“…The authors commented that there was an overall improvement in chest wall compliance and total compliance following breast reduction surgery. The mean weight of excised breast tissue in their study was 1546 g. Sood et al 4 demonstrated an improvement in inspiratory capacity, peak expiratory flow rate, and maximal voluntary ventilation. This also correlated positively with BMI; the more obese the patient was, the more the improvement there was in pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors commented that there was an overall improvement in chest wall compliance and total compliance following breast reduction surgery. The mean weight of excised breast tissue in their study was 1546 g. Sood et al 4 demonstrated an improvement in inspiratory capacity, peak expiratory flow rate, and maximal voluntary ventilation. This also correlated positively with BMI; the more obese the patient was, the more the improvement there was in pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies regarding the effect of reduction mammaplasty on pulmonary function tests reported improvements in PFTs after reduction mammaplasty, in the other hand some others reported contradictory results (1)(2)(3)(4)(5). Therefore, BMI may be the key linking whether a reduction mammmaplasty may affect PFTs, so it is worthwhile to investigate the relationship between bra cup size, BMI and PFTs in normal adult females.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Sood et al 3 found statistically significant improvement in spirometry in the parameters inspiratory capacity, peak expiratory flow and maximal voluntary ventilation (2,220g of mean weight of resected breast). These parameters were also positively correlated with body mass index: the more obese the patients, the better the parameters of lung function.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The lung function has been studied in patients undergoing reduction mammaplasty, however, few studies have evaluated objective data 3,7,8 . This can be done through lung function tests and measurement of arterial blood gases.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation